Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Profesionalisme Guru di SDN 2 Ketangga Jeraeng - Kamaruddin; Nasrullah; Mashidayati (Pendidikan Al-Gafari, 2023)
Education is business conscious and planned for realizing atmosphere learning and the learning process for students in a way active develop potency himself for own religious spiritual power, control self, personality, intelligence, morals glorious as well as necessary skills himself, society, nation, and state. Study this aims to know what is the head's strategy school to increase professionalism at SDN 2 Katanga Jeraeng. Study This is a study qualitative with a method study. Data collection techniques used that is observation (Observation), interviews, and documentation. As for technique analysis used in the study, this is analysis descriptive qualitative. The position of the teacher as an educator needs something ability capable of professional support to achieve objective education, so capable of creating changes Act sells, fine at school nor in society. Teacher professionalism can be formed through improvement programs. Enhancement of the expected capable support teachers in operating duties and roles as professional educators. The problems that occur in connection with the enhancement of teacher professionalism at SDN 2 Katanga jerking relate to weak motivation that teachers have in developing professionalism and lack of means supporting infrastructure. Enhancement of teacher professionalism is an effort made head school to increase the effectiveness of its work. With the existing enhancement, the teacher is expected to be able to increase the knowledge, skills, and attitudes of employees in carrying out their tasks as a teacher. Efforts made head school to increase teacher professionalism include seminars, training, training, workshops, and regular meetings that discuss problems/with the existing teachers.